2021
DOI: 10.1177/1934578x211016610
|View full text |Cite
|
Sign up to set email alerts
|

Andrographis paniculata (Burm. F.) Wall. Ex Nees, Andrographolide, and Andrographolide Analogues as SARS-CoV-2 Antivirals? A Rapid Review

Abstract: Drug repurposing is commonly employed in the search for potential therapeutic agents. Andrographis paniculata, a medicinal plant commonly used for symptomatic relief of the common cold, and its phytoconstituent andrographolide, have been repeatedly identified as potential antivirals against SARS-CoV-2. In light of new evidence emerging since the onset of the COVID-19 pandemic, this rapid review was conducted to identify and evaluate the current SARS-CoV-2 antiviral evidence for A. paniculata, andrographolide, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 93 publications
0
13
0
Order By: Relevance
“…Angiotensin-converting enzyme 2 (ACE-2) has been identified as one of the main receptors to which the SARS-CoV-2 virus binds (Bourgonje et al, 2020). A previous in silico prediction found that a possible mechanism of A. paniculata's beneficial effects could involve the inhibition of this receptor (Lim et al, 2021). In addition, this study has predicted the binding of AP to antiviral targets, including the spike protein-ACE-2 receptor complex, spike protein, ACE-2 receptor, RdRp, 3CLpro, PLpro, and N-protein RNA-binding domain (Lim et al, 2021).…”
Section: In Silico Studiesmentioning
confidence: 90%
See 1 more Smart Citation
“…Angiotensin-converting enzyme 2 (ACE-2) has been identified as one of the main receptors to which the SARS-CoV-2 virus binds (Bourgonje et al, 2020). A previous in silico prediction found that a possible mechanism of A. paniculata's beneficial effects could involve the inhibition of this receptor (Lim et al, 2021). In addition, this study has predicted the binding of AP to antiviral targets, including the spike protein-ACE-2 receptor complex, spike protein, ACE-2 receptor, RdRp, 3CLpro, PLpro, and N-protein RNA-binding domain (Lim et al, 2021).…”
Section: In Silico Studiesmentioning
confidence: 90%
“…A previous in silico prediction found that a possible mechanism of A. paniculata's beneficial effects could involve the inhibition of this receptor (Lim et al, 2021). In addition, this study has predicted the binding of AP to antiviral targets, including the spike protein-ACE-2 receptor complex, spike protein, ACE-2 receptor, RdRp, 3CLpro, PLpro, and N-protein RNA-binding domain (Lim et al, 2021). The findings in these in silico studies imply that AP possesses multi-pathway targets contributing to its SARS-CoV-2 antiviral properties.…”
Section: In Silico Studiesmentioning
confidence: 99%
“…Andrographolide is found to exhibit a broad spectrum of anti-osteoclastogenesis [12], hepatopancreatic and gastroprotective [23], anti-allergic, anticancer and immunomodulatory, antihyperglycemic [24], antiosteoporosis, antioxidant [25], anti-inflammatory [26,27], antimicrobial, antiviral [28], antidiarrheal, and antimalarial activity [29,30], as shown in Figure 4. development of B16 melanoma cancer cells in immunocompetent C57BL/6 mice and HT-29 tumors in mouse models.…”
Section: Structure-activity Relationship Of Analogs Of Andrographolidementioning
confidence: 99%
“…Moreover, modulation of the immune response of these combo's (herbal-synthetic agents) and their interaction with specific receptors and cellular components are being actively studied, monitored, and the data reveal the addition of their beneficial application [94]. Drugs like Remdesivir, Hydroxychloroquine, Captopril, Nafamostat in combination with AGL constituents are established to have a good antiviral activity targeting ACE-2 receptor and spike protein complex, RdRp, PL pro , 3CL pro , N-protein RNA-binding domain of SARS-CoV-2 [95][96][97][98].…”
Section: Prospective Of Herbal-chemo Drug Development: a Potential Approach For Human Immunity Enhancementmentioning
confidence: 99%